Efektivitas Terapi Guided Imagery dan Aromaterapi Pappermint Terhadap Mual Muntah Pada Ibu Hamil - Devira Putri Krismadhani; Nur Rakhmawati; Yunita Wulandari (Yayasan Jompa Research and Development, 2023)
Inconveniences in pregnancy is nauseous usual vomiting occur on beginning pregnancy. Complaint nauseous vomit occur in 60-80% primi-gravida and 40-60% in multigravida. Management nauseous vomit could conducted with given therapy non pharmacologic in the form of Guided imagery therapy and peppermint aromatherapy inhalation that is non-instructive, non-invasive, cheap, effective and no have effect detrimental side. This study aimed for knowing influence given Guided imagery therapy and peppermint aromatherapy by inhalation to drop nauseous vomit on mother pregnant. This study was a quantitative type with method quasi-experimental research with one group pre test – post test without control design. Sample totaling 48 mothers pregnant taken with Purposive Sampling technique. Results study show before given Guided imagery therapy and Peppermint aromatherapy majority mother pregnant experience nauseous vomit currently as many as 23 people (47.9%) and after given Guided Imagery Therapy and Peppermint aromatherapy majority mother pregnant reduce and no experience nauseous vomit as much mild 19 people (39.6%) and moderate 29 people (60.4%). According to Wilcoxon test shows P Value is 0.000 (<0.05). Then Ho is rejected and Ha accepted that there is effectiveness guided imagery therapy and aroma therapy papermint to nauseous vomit on mother pregnant. Keywords : Nausea, Vomiting, Guided imagery, Aromatherapy Peppermint